S75 A readily accessible CT-based score to measure amount of fibrosis in IPF. (December 2018) - Fraser, E; St Noble, V; Hoyles, R; Benamore, R; Ho, LP
Abstract : Introduction: IPF is a progressive fibro-proliferative disease that exclusively affects the lungs. Establishing extent of disease at baseline and during the clinical course has prognostic and therapeutic implications. HRCT scan provides the potential to measure the amount of fibrosis and change in character of fibrosis in a specific area of lung over time. Numerous CT-scoring systems have been designed for ILD but an easily accessible method post the 2011 ATS IPF statement has not been established. We devised a simple CT-based, visual (non-computerised) scoring method and question its reproducibility and relationship to lung function. Method: HRCTs from 44 patients with an MDT-defined diagnosis of IPF were scored independently by two ILD-specialist radiologists blinded to the clinical data. The scoring system measured the amount of four key components of UIP fibrosis – honeycombing, reticulation, traction bronchiectasis (TB), and ground glass opacification with TB (indicating fine fibrosis). Six slices, determined by specified distances from the main carina, representing the right and left upper, middle and lower lung zones, were scored for extent of the four components, and depicted as% of the specified area, to the nearest 5%. The 'Total IPF Fibrosis Score' (TIFS) was the sum score of these percentages for all the slices. Contemporaneous lung functions were measured and the composite physiological index (CPI) (Wells A 2003), which adjusts for presence of emphysema, was calculated. Results: Extent scores for each of the fibrotic parameters and the TIFS were highly reproducible between the two radiologists (all p<0.001). Bland-Altman analysis showed a lack of systemic deviation in the scores. TIFs correlated negatively with TLCO and FVC (r=0.60, p<0.03 and r=0.4, p<0.003 respectively) but not with FEV1 as expected. The closest correlation was between the TIFS and CPI (r=0.63, p<0.001, ). Conclusion: We present a simplified CT-based scoring system to measure amount of fibrosis in IPF. We show that it correlates well with lung function and is highly reproducible between two radiologists. This offers a readily available method to determine extent of disease and adds to lung function in the assessment of disease progression and response to therapy in patients with IPF.